Insan Kamil as a Model of Spiritual Perfection in Islamic Sufism - Achmad Junaedi Sitika; Hanifah Nur Inayah; Daffa Wildani Purwanto (Values: Jurnal Kajian Islam Multidisiplin, 2026)
In the rapid flow of modernization and digitalization, humans often lose their spiritual direction. This is where the concept of the Perfect Man, the perfect human, in Sufism, becomes relevant again as a model of spiritual and moral perfection. This study aims to explore the philosophical and spiritual meaning of the Perfect Man as explained by classical Sufis, such as Ibn ‘Arabi and Abdul Karim al-Jili, and highlight its relevance for character development in contemporary Islamic education. The study employed a library research approach, examining Sufi works and current academic research. The analysis shows that, according to Ibn ‘Arabi, the Perfect Man is “a mirror in which God sees Himself” (Wiwaha, 2024) and serves as a link between God and His creation. Meanwhile, al-Jili views the Perfect Man as a human capable of “realizing the divine essence within oneself through knowledge and purification of the soul” (Iqbal & Munawaroh, 2023). In a modern context, this concept is not merely mystical but can be applied as a foundation for developing Islamic morals that balance the spiritual and social dimensions. This research confirms that Insan Kamil is a paradigm of Islamic education that guides humans to achieve moral perfection and closeness to God. Integrating Sufism values into the Islamic Religious Education curriculum can be a strategy for developing individuals with Islamic character who are resilient in facing the challenges of the times.